Mathematical Model Of Energy Transferred In A Single Ball Motion In Agitation Mode - Budin, Salina (2010)
Particle size reduction process using mechanical milling method is an inefficient energy intensive process. Typically, only 1 to 5 percents of the energy supplied to the process are utilized for the size reduction of the particle, and the remaining energy is dissipated mainly into heat. Since energy is one of the predominant operating costs, a lot of efforts have been expanded to understand the mechanism of particle breakage in size reduction process in order to increase the energy efficiency. In industrial practices, this inefficiency is inevitably accepted by allowing longer processing time.